On business models, resources and exogenous (dis)continuous innovation: evidences from the mobile applications industry. (13th April 2015) - Ghezzi, Antonio; Cavallaro, Andrea; Rangone, Andrea; Balocco, Raffaello
While theories on innovation management and strategy has often focused on teaching strategists how to promote change endogenously, by taking the role of 'innovation–makers', it should be recognised that a single firm is often forced to act as an 'innovation–taker', receiving rather than driving innovations generated exogenously. The effect of external change on a firm's strategy is even more dramatic whenever change is shaped as a discontinuity. This study aims at deepening the understanding on the effect of exogenous discontinuous innovation, by investigating if and how it affects a firm's business model and its resources, competencies and capabilities (R&C&C) endowment. In addition, light is shed on the relationship between these two models under external discontinuity. The findings reveal that an exogenous discontinuous innovation acts first on the business model parameters of value proposition and financial configuration; in turn, the firm aligns its key resources, key activities, key partners and key dynamic capabilities to the emerging context.